Politics of piety : the Islamic revival and the feminist subject - Saba Mahmood (Routledge, 2017)
Politics of Piety is a groundbreaking analysis of Islamist cultural politics through the ethnography of a thriving, grassroots women's piety movement in the mosques of Cairo, Egypt. Unlike those organized Islamist activities that seek to seize or transform the state, this is a moral reform movement whose orthodox practices are commonly viewed as inconsequential to Egypt's political landscape. Saba Mahmood's compelling exposition of these practices challenges this assumption by showing how the ethical and the political are indelibly linked within the context of such movements.